Wallace Stevens : The Making of Harmonium - Buttel, Robert (Book collections on Project MUSE., 2015)
The years between 1900 and 1915 were a crucial period in Wallace Stevens' poetic career. But until Robert Buttel was given access to 30 manuscript poems written during this time, these years constituted the largest gap in our knowledge of Stevens' artistic development. These poems, as well as those printed in the Harvard Advocate, are presented in a sequence which allows the reader to view the changes in Stevens' art during this period.Originally published in 1967.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.